2016
DOI: 10.1007/s10995-016-2058-1
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity Is Not Associated with Overall Diet Quality Among Pregnant Women in NHANES 1999–2008

Abstract: In a nationally representative sample of pregnant women, 80 % lived in a fully food secure household. Improving household food security during pregnancy is a public health opportunity to improve health outcomes; however household food security status may not be associated with overall diet quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 31 publications
0
41
1
1
Order By: Relevance
“…Among the studies that investigated this association, Natamba and colleagues [38] found that a lack of social support in pregnant women with depressive symptoms was associated with FI. Poor dietary quality and/or dietary diversity and/or inadequate nutrient intake was the second most investigated outcome in eight publications (22.2%); this outcome was associated with FI in six of the publications, but in two publications, the authors found no association [14,34]. The relationship between the gestational weight gain and/or inadequate nutritional status of pregnant women was investigated, with or without an examination of pregnancy complications and nutritional consumption outcomes, in four studies (the studies published by Laraia and colleagues [9,45,48] and by Widen et al [39].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Among the studies that investigated this association, Natamba and colleagues [38] found that a lack of social support in pregnant women with depressive symptoms was associated with FI. Poor dietary quality and/or dietary diversity and/or inadequate nutrient intake was the second most investigated outcome in eight publications (22.2%); this outcome was associated with FI in six of the publications, but in two publications, the authors found no association [14,34]. The relationship between the gestational weight gain and/or inadequate nutritional status of pregnant women was investigated, with or without an examination of pregnancy complications and nutritional consumption outcomes, in four studies (the studies published by Laraia and colleagues [9,45,48] and by Widen et al [39].…”
Section: Resultsmentioning
confidence: 94%
“…Outcomes related to consumption and dietary quality were the most investigated after stress and depressionrelated events [10,14,31,34,41,45,54,63], showing the authors' concern with verifying dietary adequacy among pregnant women and whether dietary adequacy is truly associated with FI. Since most of the instruments that were used to assess FI in the studies included in this review relied on psychometric methodologies to measure access to food in sufficient quantity and quality, pregnant women's perceptions of access to adequate food did not necessarily correspond to the actual quality or fitness of the diet they consumed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it might have been better to assess whether nutritional intake is sufficient. For future studies, we suggest using the Healthy mother, healthy baby—nutritional questionnaire for pregnant women (https://www.figo.org) or the Alternate Healthy Eating Index modified for Pregnancy (AHEI‐P) . Nevertheless, the data were collected using a standardized format, and any inconsistency in reporting would have been equally distributed, regardless of maternal age.…”
Section: Discussionmentioning
confidence: 99%
“…12 In this review the prevalence of food insecurity in women during the gestational period ranged from 9.0% to 87.9% (Table 1), with the lowest prevalence found in developed countries and the highest prevalence in underdeveloped or developing countries. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Although there are some studies on food insecurity during the gestational period, there is still little knowledge about the effects of this insecurity on maternal and child health. Food insecurity in the gestational period is associated with anemia, pre-gestational and gestational anthropometric nutritional status, birth defects, maternal depression/anxiety disorders in pregnancy, gestational complications (diabetes, hypertension and obesity), gestational weight gain, food intake, low birth weight and postpartum depression and suicide.…”
Section: Food Insecurity During the Gestational Periodmentioning
confidence: 99%